Construção dos saberes sobre as práticas avaliativas dos professores de Educação Física. - Bermudes, Roberta (2010)
The evaluation has been an applicant topic in the discussions about the pedagogical practices in school and also in the Physic l Education (PE) area. The choice of the theme is justified as we consider necessary to uncover and minimize the dominant speech about the depreciation of knowledge and practices of teachers. This is a descriptive research, a case study where we approach the Physical Education teachers from municipal schools of Pelotas RS, which are inserted in the project of implementation of a 9-year-long teaching in basic education. The tool used for this collection of information was a semi-structured interview, which was recorded, transcribed, and afterwards, interpreted through the analysis of content. During the literature review, we signed: the importance of the knowledge produced by each teacher, the knowledge about the habitus of each agent that lives in a social space; the abilities of the PE teachers who act in the schools, among them, in special, the ability of evaluate; and the knowledge about the cycles or stages of each stage lived by the teachers inside their careers, understanding the characterization of the teaching trajectory in lifecycles and/or professional development. For the data analysis, categories that discuss the construction of knowledge about the evaluation practices in the teachers career were extracted. We can conclude that teachers build their knowledge along with their professional course, gradually attaching this knowledge to their pedagogical action, through the mobilization of it.